The Dual Role of Early Childhood Teachers as Health Cadres in Reducing Stunting: - - Nurul Hakimah; Siti Rahayu Nadhiroh; Nandia Firsty Dhorta; Tapriadi; Fitria Dhenok Palupi; Indri Hapsari; Ibnu Fajar; Juin Hadisuyitno (Universitas Airlangga, 2022)
Background: The role of early childhood education teachers (PAUD) is getting bigger in areas related to child nutrition and become potential contributors in improving and reducing stunting cases in children under five. The purpose of this study is how to promote health through the right food for PAUD-aged children. The role of PAUD teachers as well as health cadres is to become best practice in efforts to reduce stunting in the Malang City, Indonesia. Methods: This research is an analytic observational cross sectional design, using 150 PAUD teachers as well as health cadres who carry out best practice efforts to reduce stunting through evidence-based in-depth interviews. Results: The best practices that have been implemented are : the number of PAUD-age children who receive PMT directly; the ease of delivery of health promotion to the community, especially parents or child caretakers; higher community compliance; and a significant increase in children's weight and height. The impact and output of the dual role of PAUD teachers as health cadres in reducing stunting is more effective. Conclusion: This dual role of early childhood teachers as health cadres needs to be appreciated, defined, and rewarded by national authorities, based on local needs, and programmed according to policy-based evidence, such as in the formation of the Team for the Acceleration of Stunting Reduction (TPPS).